Pengaruh Perputaran Modal Kerja Terhadap Sisa Hasil Usaha Pada Koperasi Kredit Serviam Cabang Oebufu Kupang - Theresia Fouk Leu (CV. ITTC INDONESIA, 2023)
The problem in this study is the decline in SHU in 2021 in percentage terms. The formulation of the problem in this research is how to influence working capital turnover on the remaining business results of the Serviam Credit Cooperative, Oebufu Kupang Branch. The purpose of this study was to determine the effect of working capital turnover on the Oebufu Kupang Branch Serviam Credit Cooperative SHU in 2015-2021. Data collection techniques using documentation studies and interviews. The data that has been collected is analyzed using simple linear regression with the help of the program (SPSS) using simple linear regression analysis techniques. Based on the results of data analysis, it shows that the effect of working capital turnover on SHU can be proven from the results of simple linear regression analysis Y = 1003282801.494 +21021529.754X, this equation can be explained by the value of the coefficient b called the coefficient of the regression direction and expresses the average change in variable Y for each change in variable x by one rupiah. Change is an increase in the value of b marked positive and a decrease if b is negative. From the calculation results, it is obtained that b = 1003282801.494 is positive, which means that every x (working capital turnover) increases by Rp. 1, then the variable y (SHU). An increase of Rp. 1003282801.494, conversely if the variable x (working capital turnover) decreases by Rp. 1, then the variable y (SHU) decreases by Rp. 1003282801.494, the value of the regression coefficient X = a sig value of 0.088 and an alpha of 0.05. From this value it shows that there is no significant effect between working capital and the remaining results of operations (SHU) because it is significantly greater than alpha (0.946 > 0.05) so it was decided to accept Ho and reject Ha, which means that working capital has no significant effect on SHU The result of the coefficient of determination (R Square/r2) is 0.000. The value of R2 = 0.000 means that the contribution (share) of the working capital turnover variable (X) to variation (up and down) of the SHU variable (Y) to the Oebufu Kupang Branch Serviam Credit Cooperative is 0.000%, there are no other factors.